Information System Quality and Student Satisfaction: An Empirical Analysis of the SATU USU System at Universitas Sumatera Utara - Adika Fajar Putra; Triara Juniarsih (Journal Of Management Analytical and Solution (JoMAS), 2026)
This study investigates the influence of information quality within the SATUUSU academic information system on student satisfaction at the Faculty ofVocational Studies, Universitas Sumatera Utara. The research employs aquantitative approach using Partial Least Squares–Structural Equation Modeling(PLS-SEM) to analyze the relationship between information quality and studentsatisfaction. A total of 105 respondents were selected from a population of 2,500active students using the Slovin formula with a 10% margin of error. Informationquality was measured through five indicators: accuracy, completeness,relevance, clarity, and timeliness. Student satisfaction was assessed usingindicators of ease of use, interface satisfaction, perceived usefulness, systemsuitability, and overall satisfaction. The measurement model results demonstratestrong validity and reliability, indicated by outer loading values exceeding 0.70,Average Variance Extracted (AVE) values above 0.50, and composite reliabilityvalues greater than 0.90. The structural model analysis shows an R-square valueof 0.802, indicating that information quality explains a substantial proportion ofthe variance in student satisfaction. Bootstrapping results confirm a significantpositive effect of information quality on student satisfaction (β = 0.896; t =30.165; p < 0.001). These findings highlight the critical role of high-qualityinformation in improving user satisfaction with academic information systems inhigher education institutions.